Rachel C. answered • 06/28/19

High School Math Teacher Looking To Help Your Student Succeed

Let's use substitution. Since x = -4, anywhere we see an 'x', we will replace it with -4. As y = 2, anywhere we see a 'y', we will replace it with a 2.

So -3x^{2}y + 4x becomes

= [ -3 * ( -4 )^{2} * 2 ] + [ 4 * ( -4 )]

Following order of operations, PEMDAS, within the parentheses, we have an exponent to simplify

= [ -3 * 16 * 2 ] + [ 4 * -4 ]

= [ -96 ] + [ -16 ]

= -112

Therefore, when x = -4 and y = 2 for -3x^{2}y + 4x, your answer is -112